167k views
0 votes
In a previous exercise we formulated a model for learning in the form of the differential equation dp dt = k(m − p) where p(t) measures the performance of someone learning a skill after a training time t, m is the maximum level of performance, and k is a positive constant. solve this differential equation to find an expression for p(t). (use p for p(t). assume that p(0) = 0.) incorrect: your answer is incorrect.

User Coen Damen
by
5.9k points

2 Answers

5 votes
Hi there!


(dP)/(dt) = k(M-P)


(dP)/(M-P) = k


\textbf{Integrate\: both \:sides\: of\: th'\: Eqn.} :-


\int (dP)/(M-P) = \int kdt


\ln|M-P| = kt + C


\ln|M-P| = -kt - C

Since,

u = M - P \implies du = -1dP \implies dP = -du


\int (dP)/(M-P) \\e \ln|M - P|


\textbf{Applying\: definition \:of\: logarithm} :-


\ln|M-P| = -kt - C


|M - P| = e^(-kt - C)


M - P = \pm e^(-kt - C)


\textbf{Further solving} :-


M - P = \pm e^(-kt - C)


M - P = \pm e^(- C - kt)


M - P = \pm e^(- C + (- kt))


M - P = \pm e^(- C) × e^(- kt)


M - P = Ke^(- kt)


M = Ke^(- kt) + P


P = M - Ke^(- kt)


\textbf{Let \:P(0) \:= \:0, \:then \:set\: t\: =\: 0\: and\: P \:= \:0} :-


0 = M - Ke^(- k × 0)


0 = M - K × 1


M = K

Substitute th' following value in Original Eq :-


\boxed{P = M - Me^(-kt)}


~ Hope it helps!
User Heroxbd
by
6.4k points
4 votes
I assume you mean


(dP)/(dt) = k(M-P)

ANSWER
An expression for P(t) is


P = M - Me^(-kt)

Step-by-step explanation
This is a separable differential equation. Treat M and k as constants. Then we can divide both sides by M - P to get the P term with the differential dP and multiply both sides by dt to separate dt from the P terms


\begin{aligned} (dP)/(dt) &= k(M-P) \\ (dP)/(M-P) &= k\, dt \end{aligned}

Integrate both sides of the equation.


\begin{aligned} \int (dP)/(M-P) &= \int k\, dt \\ -\ln|M-P| &= kt + C \\ \ln|M-P| &= -kt - C\end{aligned}

Note that for the left-hand side, u-substitution gives us


u = M - P \implies du = -1dP \implies dP = -du

hence why
\int (dP)/(M-P) \\e \ln|M - P|

Now we use the definition of the logarithm to convert into exponential form.

The definition is


\ln(a) = b \iff \log_e(a) = b \iff e^b = a

so applying it here, we get


\begin{aligned} \ln|M-P| &= -kt - C \\ |M - P| &= e^(-kt - C) \\ M - P &= \pm e^(-kt - C) \end{aligned}

Exponent properties can be used to address the constant C. We use
x^(a) \cdot x^(b) = x^(a+b) here:


\begin{aligned} M - P &= \pm e^(-kt - C) \\ M - P &= \pm e^(- C - kt) \\ M - P &= \pm e^(- C + (- kt)) \\ M - P &= \pm e^(- C) \cdot e^(- kt) \\ M - P &= Ke^(- kt) && (\text{\footnotesize Let $K = \pm e^(-kt)$ }) \\ M &= Ke^(- kt) + P\\ P &= M - Ke^(- kt) \end{aligned}

If we assume that P(0) = 0, then set t = 0 and P = 0


\begin{aligned} 0 &= M - Ke^(- k\cdot 0) \\ 0 &= M - K \cdot 1 \\ M &= K \end{aligned}

Substituting into our original equation, we get our final answer of


P = M - Me^(-kt)
User Tstr
by
5.7k points